Targeting LINC00673 expression triggers cellular senescence in lung cancer - Roth, Anna; Warth, Arne; Schnabel, Philipp Albert; Muley, Thomas; Meister, Michael; Zabeck, Heike; Hoffmann, Hans (RNA biology, 2018)
Aberrant expression of noncoding RNAs plays a critical role during tumorigenesis. To uncover novel functions of long non-coding RNA (lncRNA) in lung adenocarcinoma, we used a microarray-based screen identifying LINC00673 with elevated expression in matched tumor versus normal tissue. We report that loss of LINC00673 is sufficient to trigger cellular senescence, a tumor suppressive mechanism associated with permanent cell cycle arrest, both in lung cancer and normal cells in a p53-dependent manner. LINC00673-depleted cells fail to efficiently transit from G1- to S-phase. Using a quantitative proteomics approach, we confirm the modulation of senescence-associated genes as a result of LINC00673 knockdown. In addition, we uncover that depletion of p53 in normal and tumor cells is sufficient to overcome LINC00673-mediated cell cycle arrest and cellular senescence. Furthermore, we report that overexpression of LINC00673 reduces p53 translation and contributes to the bypass of Ras-induced senescence. In summary, our findings highlight LINC00673 as a crucial regulator of proliferation and cellular senescence in lung cancer.
Gesehen am 18.04.2019